Self-cleaning glaze using glaze frit, self-cleaning ceramic and preparation method thereof
By using potassium feldspar, nano zinc oxide and other materials to prepare glaze fuses, combined with nano-hydroxyapatite modified bifunctional bodies and modified fillers, the problems of poor self-cleaning performance and low stability of ceramics are solved, and the excellent anti-slip, wear resistance and antibacterial properties of ceramics are achieved, as well as significant improvement in stability under acid, alkali and scratch conditions.
Patent Information
- Application Number
- CN202411782729.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The existing ceramics have poor self-cleaning performance, and are difficult to coordinately improve the anti-slip, wear resistance and antibacterial properties, and the product has low stability under acid and alkali and scratch conditions.
The glaze fuse prepared by potassium feldspar, nano zinc oxide, calcite and quartz was used to combine bifunctional bodies modified based on nano-hydroxyapatite, modified filler agent and calcium carbonate, and self-cleaning glaze was prepared by wet ball milling, and then applied to the ceramic blank and sintered.
The anti-slip, wear and antibacterial properties of ceramics are significantly improved, and the stability is significantly improved under acid and alkali and scratch conditions.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramics, and in particular to a self-cleaning glaze using glaze frit, a self-cleaning ceramic and a preparation method thereof. Background Art
[0002] Ceramics is a general term for pottery and porcelain. Common ceramic materials include clay, alumina, kaolin, etc. Ceramic materials are generally hard but have poor plasticity. In addition to being used in tableware and decoration, ceramics also play an important role in the development of science and technology. Ceramic raw materials are made by quenching clay, a large amount of original resources on the earth.
[0003] The existing ceramics prepared from frit glazes have poor self-cleaning properties, and the anti-slip, wear-resistant and antibacterial properties are difficult to improve in a coordinated manner. At the same time, the product stability is low and the stability is poor under acid, alkali and scratch conditions, which limits the product's use efficiency. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a self-cleaning glaze using glaze frit, self-cleaning ceramics and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution:
[0006] The present invention provides a glaze frit, comprising the following raw materials in parts by weight:
[0007] 10-15 parts of potassium feldspar, 8-12 parts of nano zinc oxide, 5-7 parts of calcite and 4-6 parts of quartz.
[0008] The present invention also provides a self-cleaning glaze, comprising the following raw materials in parts by weight:
[0009] 15-20 parts of bifunctional body modified based on nano-hydroxyapatite, 10-15 parts of glaze frit, 6-9 parts of modified filler, 4-7 parts of wollastonite and 3-5 parts of calcium carbonate;
[0010] The glaze frit comprises the following raw materials in parts by weight:
[0011] 10-15 parts of potassium feldspar, 8-12 parts of nano zinc oxide, 5-7 parts of calcite and 4-6 parts of quartz.
[0012] Preferably, the preparation method of the bifunctional body based on nano-hydroxyapatite modification is:
[0013] S01: immersing the nano-magnesium oxide into a sufficient amount of sodium silicate solution, the immersion power is 350-400W, the immersion time is 20-30min, and the immersion is completed to obtain the nano-magnesium oxide liquid;
[0014] S02: Stir and mix the silicon carbide fiber in the acid solution, then wash, filter and dry to obtain dry silicon carbide fiber; add 5 to 8 parts of dry silicon carbide fiber and 3 to 5 parts of nano-magnesium oxide liquid to 7 to 11 parts of dopamine hydrochloride solution by weight and stir to obtain silicon carbide fiber / nano-magnesium oxide composite liquid;
[0015] S03: The silicon carbide fiber / nano-magnesium oxide composite liquid and the nano-hydroxyapatite agent are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1000 r / min for 2 h. After the ball milling is completed, the mixture is filtered and dried to obtain a nano-hydroxyapatite-modified bifunctional body.
[0016] Preferably, the mass fraction of the sodium silicate solution is 2-5%; the acid solution is a sulfuric acid solution with a mass fraction of 5%; and the mass fraction of the dopamine hydrochloride solution is 3-5%.
[0017] Preferably, the preparation method based on nano-hydroxyapatite agent is:
[0018] According to weight, 3 to 5 parts of nano-hydroxyapatite and 1 to 2 parts of citric acid are added to 5 to 8 parts of 5% sodium lignin sulfonate solution, and then 2 to 4 parts of nano-mica powder and 1 to 2 parts of samarium nitrate are added to improve the ball milling treatment. After the ball milling is completed, the mixture is filtered and dried to obtain a nano-hydroxyapatite agent.
[0019] Preferably, the ball milling speed of the improved ball milling treatment is 550-750 r / min, and the ball milling is 2-3 hours.
[0020] Preferably, the preparation method of the modified filler is:
[0021] S11: Evenly blend nano-titanium dioxide, chitosan solution and silane coupling agent KH550 in a weight ratio of (3-4):(6-8):1 to obtain nano-titanium dioxide liquid;
[0022] S12: adding 3 to 5 parts of zirconium silicate and 2 to 3 parts of europium nitrate to 5 to 8 parts of lanthanum chloride solution by weight, and then adding 1 to 2 parts of sodium carboxymethyl cellulose, and mixing well to obtain a modifier;
[0023] The modifier and nano titanium dioxide liquid are stirred and modified in a weight ratio of 2:(5-6). After the stirring is completed, the modified filler is filtered and dried to obtain a modified filler.
[0024] Preferably, the mass fraction of the chitosan solution is 2-5%; the mass fraction of the lanthanum chloride solution is 3-5%; the stirring temperature of the stirring modification treatment is 55-60°C, the stirring time is 20-30min, and the stirring speed is 550-750r / min.
[0025] The present invention also provides a method for preparing a self-cleaning ceramic, comprising the following steps:
[0026] Step 1: 4-7 parts of clay, 5-8 parts of porcelain stone, 8-12 parts of calcined talc and 10-15 parts of illite are mixed and wet-milled by weight at a ball milling speed of 1500r / min for 1h. After the ball milling is completed, the mixture is put into a mold for molding at a molding pressure of 15MPa for 2h, and demolded to obtain a ceramic body;
[0027] Step 2: melting 10-15 parts of potassium feldspar, 8-12 parts of nano zinc oxide, 5-7 parts of calcite and 4-6 parts of quartz by weight until the raw materials are completely melted, and then quenching with water to obtain a glaze frit;
[0028] 15-20 parts of nano-hydroxyapatite modified bifunctional body, 10-15 parts of glaze frit, 6-9 parts of modified filler, 4-7 parts of wollastonite and 3-5 parts of calcium carbonate are wet-milled by weight at a ball milling speed of 1500 r / min for 1 hour to obtain a self-cleaning glaze;
[0029] Step 3: Apply the self-cleaning glaze to the ceramic body, the amount of glaze applied is 550-580g / m 2 After the application is completed, the ceramic is sintered for 2 hours at a temperature of 1250°C to obtain self-cleaning ceramics.
[0030] The present invention also provides a self-cleaning ceramic, which is prepared by the preparation method of the self-cleaning ceramic.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. The glaze frit of the present invention is prepared by blending potassium feldspar, nano zinc oxide, calcite and quartz. The raw materials are blended to assist in the preparation of the glaze frit. The glaze frit is used in combination with a bifunctional body based on nano hydroxyapatite modification, a modified filler, wollastonite and calcium carbonate. The synergistic effect of the raw materials is used to enhance the performance of the product. The ceramic body is formed by wet ball milling of clay, porcelain stone, calcite and illite. The ceramic body is combined with a self-cleaning glaze to enhance the anti-skid, wear-resistant and antibacterial properties of the product. At the same time, the performance of the three is coordinated and improved, and the stability of the product under acid, alkali and scratch conditions is remarkable.
[0033] 2. The bifunctional body modified by nano-hydroxyapatite adopts silicon carbide fiber / nano-magnesium oxide composite liquid and nano-hydroxyapatite agent for ball milling treatment. The silicon carbide fiber in the silicon carbide fiber / nano-magnesium oxide composite liquid is activated and improved by acid solution. At the same time, nano-magnesium oxide is fully immersed in sodium silicate solution to optimize the stability of nano-magnesium oxide, thereby facilitating better coordination with silicon carbide fiber. The needle-like structure of silicon carbide fiber is coordinated with nano-magnesium oxide, and the two are blended and then improved by ball milling based on nano-hydroxyapatite agent. Nano-hydroxyapatite is used as the matrix raw material based on nano-hydroxyapatite agent, and nano-mica powder and samarium nitrate are blended and enhanced by blending and strengthening with lamellar nano-mica powder, and samarium nitrate is blended and coordinated with citric acid and sodium lignin sulfonate solution. Through the mutual coordination and mutual assistance between the raw materials, the coordinated compounding effect of nano-hydroxyapatite agent and silicon carbide fiber / nano-magnesium oxide composite liquid is further enhanced, so that the performance of the product can be further coordinated and improved, the anti-slip and antibacterial properties of the product are optimized, and the performance stability of the product is improved at the same time;
[0034] 3. The modified filler is prepared by mixing nano-titanium dioxide with chitosan solution and silane coupling agent KH550, and then improved and enhanced by a modifier. The zirconium silicate and europium nitrate in the modifier are combined with lanthanum chloride solution. Through the mutual matching and assistance between the raw materials, the modified filler obtained has a synergistic effect with the bifunctional body based on nano-hydroxyapatite modification, thereby further improving the performance of the product. DETAILED DESCRIPTION
[0035] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] A glaze frit of the present embodiment includes the following raw materials in parts by weight:
[0037] 10-15 parts of potassium feldspar, 8-12 parts of nano zinc oxide, 5-7 parts of calcite and 4-6 parts of quartz.
[0038] A self-cleaning glaze of this embodiment includes the following raw materials in parts by weight:
[0039] 15-20 parts of bifunctional body modified based on nano-hydroxyapatite, 10-15 parts of glaze frit, 6-9 parts of modified filler, 4-7 parts of wollastonite and 3-5 parts of calcium carbonate;
[0040] The glaze frit comprises the following raw materials in parts by weight:
[0041] 10-15 parts of potassium feldspar, 8-12 parts of nano zinc oxide, 5-7 parts of calcite and 4-6 parts of quartz.
[0042] The preparation method of the bifunctional body based on nano-hydroxyapatite modification in this embodiment is:
[0043] S01: immersing the nano-magnesium oxide into a sufficient amount of sodium silicate solution, the immersion power is 350-400W, the immersion time is 20-30min, and the immersion is completed to obtain the nano-magnesium oxide liquid;
[0044] S02: Stir and mix the silicon carbide fiber in the acid solution, then wash, filter and dry to obtain dry silicon carbide fiber; add 5 to 8 parts of dry silicon carbide fiber and 3 to 5 parts of nano-magnesium oxide liquid to 7 to 11 parts of dopamine hydrochloride solution by weight and stir to obtain silicon carbide fiber / nano-magnesium oxide composite liquid;
[0045] S03: The silicon carbide fiber / nano-magnesium oxide composite liquid and the nano-hydroxyapatite agent are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1000 r / min for 2 h. After the ball milling is completed, the mixture is filtered and dried to obtain a nano-hydroxyapatite-modified bifunctional body.
[0046] The mass fraction of the sodium silicate solution in this embodiment is 2-5%; the acid solution is a sulfuric acid solution with a mass fraction of 5%; and the mass fraction of the dopamine hydrochloride solution is 3-5%.
[0047] The preparation method of the nano-hydroxyapatite agent in this embodiment is:
[0048] According to weight, 3 to 5 parts of nano-hydroxyapatite and 1 to 2 parts of citric acid are added to 5 to 8 parts of 5% sodium lignin sulfonate solution, and then 2 to 4 parts of nano-mica powder and 1 to 2 parts of samarium nitrate are added to improve the ball milling treatment. After the ball milling is completed, the mixture is filtered and dried to obtain a nano-hydroxyapatite agent.
[0049] The ball milling speed of the improved ball milling process in this embodiment is 550-750 r / min, and the ball milling is performed for 2-3 hours.
[0050] The preparation method of the modified filler of this embodiment is:
[0051] S11: Evenly blend nano-titanium dioxide, chitosan solution and silane coupling agent KH550 in a weight ratio of (3-4):(6-8):1 to obtain nano-titanium dioxide liquid;
[0052] S12: adding 3 to 5 parts of zirconium silicate and 2 to 3 parts of europium nitrate to 5 to 8 parts of lanthanum chloride solution by weight, and then adding 1 to 2 parts of sodium carboxymethyl cellulose, and mixing well to obtain a modifier;
[0053] The modifier and nano titanium dioxide liquid are stirred and modified in a weight ratio of 2:(5-6). After the stirring is completed, the modified filler is filtered and dried to obtain a modified filler.
[0054] The mass fraction of the chitosan solution in this embodiment is 2-5%; the mass fraction of the lanthanum chloride solution is 3-5%; the stirring temperature of the stirring modification treatment is 55-60°C, the stirring time is 20-30min, and the stirring speed is 550-750r / min.
[0055] A method for preparing a self-cleaning ceramic in this embodiment comprises the following steps:
[0056] Step 1: 4-7 parts of clay, 5-8 parts of porcelain stone, 8-12 parts of calcined talc and 10-15 parts of illite are mixed and wet-milled by weight at a ball milling speed of 1500r / min for 1h. After the ball milling is completed, the mixture is put into a mold for molding at a molding pressure of 15MPa for 2h, and demolded to obtain a ceramic body;
[0057] Step 2: melting 10-15 parts of potassium feldspar, 8-12 parts of nano zinc oxide, 5-7 parts of calcite and 4-6 parts of quartz by weight until the raw materials are completely melted, and then quenching with water to obtain a glaze frit;
[0058] 15-20 parts of nano-hydroxyapatite modified bifunctional body, 10-15 parts of glaze frit, 6-9 parts of modified filler, 4-7 parts of wollastonite and 3-5 parts of calcium carbonate are wet-milled by weight at a ball milling speed of 1500 r / min for 1 hour to obtain a self-cleaning glaze;
[0059] Step 3: Apply the self-cleaning glaze to the ceramic body, the amount of glaze applied is 550-580g / m 2 After the application is completed, the ceramic is sintered for 2 hours at a temperature of 1250°C to obtain self-cleaning ceramics.
[0060] The self-cleaning ceramic of this embodiment is prepared by the above-mentioned method for preparing the self-cleaning ceramic.
[0061] Example 1: A glaze frit, comprising the following raw materials in parts by weight:
[0062] 10 parts of potassium feldspar, 8 parts of nano zinc oxide, 5 parts of calcite and 4 parts of quartz.
[0063] A self-cleaning glaze comprises the following raw materials in parts by weight:
[0064] 15 parts of nano-hydroxyapatite-modified bifunctional body, 10 parts of glaze frit, 6 parts of modified filler, 4 parts of wollastonite and 3 parts of calcium carbonate;
[0065] The glaze frit comprises the following raw materials in parts by weight:
[0066] 10 parts of potassium feldspar, 8 parts of nano zinc oxide, 5 parts of calcite and 4 parts of quartz.
[0067] The preparation method of the bifunctional body based on nano-hydroxyapatite modification in this embodiment is:
[0068] S01: immerse the nano-magnesium oxide into a sufficient amount of sodium silicate solution, immerse it fully, the immersion power is 350W, the immersion time is 20min, and the immersion is completed to obtain the nano-magnesium oxide liquid;
[0069] S02: Stir the silicon carbide fiber in the acid solution and mix it thoroughly, then wash it with water, filter it, and dry it to obtain dry silicon carbide fiber; add 5 parts of dry silicon carbide fiber and 3 parts of nano-magnesium oxide liquid to 7 parts of dopamine hydrochloride solution by weight and stir them thoroughly to obtain silicon carbide fiber / nano-magnesium oxide composite liquid;
[0070] S03: The silicon carbide fiber / nano-magnesium oxide composite liquid and the nano-hydroxyapatite agent are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1000 r / min for 2 h. After the ball milling is completed, the mixture is filtered and dried to obtain a nano-hydroxyapatite-modified bifunctional body.
[0071] The mass fraction of the sodium silicate solution in this embodiment is 2%; the acid solution is a sulfuric acid solution with a mass fraction of 5%; and the mass fraction of the dopamine hydrochloride solution is 3%.
[0072] The preparation method of the nano-hydroxyapatite agent in this embodiment is:
[0073] According to weight, 3 parts of nano-hydroxyapatite and 1 part of citric acid are added to 5 parts of 5% sodium lignin sulfonate solution, and then 2 parts of nano-mica powder and 1 part of samarium nitrate are added to improve the ball milling treatment. After the ball milling is completed, the mixture is filtered and dried to obtain a nano-hydroxyapatite agent.
[0074] The ball milling speed of the ball milling improvement treatment in this embodiment is 550r / min, and the ball milling is 2h.
[0075] The preparation method of the modified filler of this embodiment is:
[0076] S11: Evenly blending nano-titanium dioxide, chitosan solution and silane coupling agent KH550 in a weight ratio of 3:6:1 to obtain nano-titanium dioxide liquid;
[0077] S12: adding 3 parts of zirconium silicate and 2 parts of europium nitrate to 5 parts of lanthanum chloride solution by weight, and then adding 1 part of sodium carboxymethyl cellulose, and mixing well to obtain a modifier;
[0078] The modifier and nano titanium dioxide liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the modified filler is filtered and dried to obtain a modified filler.
[0079] The mass fraction of the chitosan solution in this embodiment is 2%; the mass fraction of the lanthanum chloride solution is 3%; the stirring temperature of the stirring modification treatment is 55° C., the stirring time is 20 min, and the stirring speed is 550 r / min.
[0080] A method for preparing a self-cleaning ceramic comprises the following steps:
[0081] Step 1: 4 parts of clay, 5 parts of porcelain stone, 8 parts of calcined talc and 10 parts of illite are mixed and wet-milled by weight at a ball milling speed of 1500 r / min for 1 hour. After the ball milling is completed, the mixture is put into a mold for molding at a molding pressure of 15 MPa for 2 hours, and demolded to obtain a ceramic body;
[0082] Step 2: melting 10 parts of potassium feldspar, 8 parts of nano zinc oxide, 5 parts of calcite and 4 parts of quartz by weight until the raw materials are completely melted, and then quenching with water to obtain a glaze frit;
[0083] 15 parts of nano-hydroxyapatite-modified bifunctional body, 10 parts of glaze frit, 6 parts of modified filler, 4 parts of wollastonite and 3 parts of calcium carbonate were wet-milled by weight at a ball milling speed of 1500 r / min for 1 hour to obtain a self-cleaning glaze;
[0084] Step 3: Apply the self-cleaning glaze to the ceramic body, the amount of glaze applied is 550g / m 2 After the application is completed, the ceramic is sintered for 2 hours at a temperature of 1250°C to obtain self-cleaning ceramics.
[0085] The self-cleaning ceramic of this embodiment is prepared by the above-mentioned method for preparing the self-cleaning ceramic.
[0086] Example 2: A glaze frit, comprising the following raw materials in parts by weight:
[0087] 15 parts of potassium feldspar, 12 parts of nano zinc oxide, 7 parts of calcite and 6 parts of quartz.
[0088] A self-cleaning glaze comprises the following raw materials in parts by weight:
[0089] 20 parts of nano-hydroxyapatite-modified bifunctional body, 15 parts of glaze frit, 9 parts of modified filler, 7 parts of wollastonite and 5 parts of calcium carbonate;
[0090] The glaze frit comprises the following raw materials in parts by weight:
[0091] 15 parts of potassium feldspar, 12 parts of nano zinc oxide, 7 parts of calcite and 6 parts of quartz.
[0092] The preparation method of the bifunctional body based on nano-hydroxyapatite modification in this embodiment is:
[0093] S01: immersing the nano-magnesium oxide into a sufficient amount of sodium silicate solution, the immersion power is 400W, the immersion time is 30min, and the immersion is completed to obtain the nano-magnesium oxide solution;
[0094] S02: Stir the silicon carbide fiber in the acid solution and mix it thoroughly, then wash it with water, filter it and dry it to obtain dry silicon carbide fiber; add 8 parts of dry silicon carbide fiber and 5 parts of nano-magnesium oxide liquid to 11 parts of dopamine hydrochloride solution by weight and stir them thoroughly to obtain silicon carbide fiber / nano-magnesium oxide composite liquid;
[0095] S03: The silicon carbide fiber / nano-magnesium oxide composite liquid and the nano-hydroxyapatite agent are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1000 r / min for 2 h. After the ball milling is completed, the mixture is filtered and dried to obtain a nano-hydroxyapatite-modified bifunctional body.
[0096] The mass fraction of the sodium silicate solution in this embodiment is 5%; the acid solution is a sulfuric acid solution with a mass fraction of 5%; and the mass fraction of the dopamine hydrochloride solution is 5%.
[0097] The preparation method of the nano-hydroxyapatite agent in this embodiment is:
[0098] According to weight, 5 parts of nano-hydroxyapatite and 2 parts of citric acid are added to 8 parts of 5% sodium lignin sulfonate solution, and then 4 parts of nano-mica powder and 2 parts of samarium nitrate are added to improve the ball milling treatment. After the ball milling is completed, the mixture is filtered and dried to obtain a nano-hydroxyapatite agent.
[0099] The ball milling speed of the improved ball milling process in this embodiment is 750 r / min, and the ball milling is performed for 3 h.
[0100] The preparation method of the modified filler of this embodiment is:
[0101] S11: Evenly blending nano-titanium dioxide, chitosan solution and silane coupling agent KH550 in a weight ratio of 4:8:1 to obtain nano-titanium dioxide liquid;
[0102] S12: adding 5 parts of zirconium silicate and 3 parts of europium nitrate to 8 parts of lanthanum chloride solution by weight, and then adding 2 parts of sodium carboxymethyl cellulose, and mixing well to obtain a modifier;
[0103] The modifier and nano titanium dioxide liquid are stirred and modified in a weight ratio of 2:6. After the stirring is completed, the modified filler is filtered and dried to obtain a modified filler.
[0104] The mass fraction of the chitosan solution in this embodiment is 5%; the mass fraction of the lanthanum chloride solution is 5%; the stirring temperature of the stirring modification treatment is 60° C., the stirring time is 30 min, and the stirring speed is 750 r / min.
[0105] A method for preparing a self-cleaning ceramic comprises the following steps:
[0106] Step 1: 7 parts of clay, 8 parts of porcelain stone, 12 parts of calcined talc and 15 parts of illite are mixed and wet-milled by weight at a ball milling speed of 1500 r / min for 1 hour. After the ball milling is completed, the mixture is put into a mold for molding at a molding pressure of 15 MPa for 2 hours, and demolded to obtain a ceramic body;
[0107] Step 2: melting 15 parts of potassium feldspar, 12 parts of nano zinc oxide, 7 parts of calcite and 6 parts of quartz by weight until the raw materials are completely melted, and then quenching with water to obtain a glaze frit;
[0108] 20 parts of nano-hydroxyapatite-modified bifunctional body, 15 parts of glaze frit, 9 parts of modified filler, 7 parts of wollastonite and 5 parts of calcium carbonate were wet-milled by weight at a ball milling speed of 1500 r / min for 1 hour to obtain a self-cleaning glaze;
[0109] Step 3: Apply the self-cleaning glaze to the ceramic body, the amount of glaze applied is 580g / m 2 After the application is completed, the ceramic is sintered for 2 hours at a temperature of 1250°C to obtain self-cleaning ceramics.
[0110] The self-cleaning ceramic of this embodiment is prepared by the above-mentioned method for preparing the self-cleaning ceramic.
[0111] Example 3: A glaze frit, comprising the following raw materials in parts by weight:
[0112] 12.5 parts of potassium feldspar, 10 parts of nano zinc oxide, 6 parts of calcite and 5 parts of quartz.
[0113] A self-cleaning glaze of this embodiment includes the following raw materials in parts by weight:
[0114] 17.5 parts of nano-hydroxyapatite-modified bifunctional body, 12.5 parts of glaze frit, 7.5 parts of modified filler, 5.5 parts of wollastonite and 4 parts of calcium carbonate;
[0115] The glaze frit comprises the following raw materials in parts by weight:
[0116] 12.5 parts of potassium feldspar, 10 parts of nano zinc oxide, 6 parts of calcite and 5 parts of quartz.
[0117] The preparation method of the bifunctional body based on nano-hydroxyapatite modification in this embodiment is:
[0118] S01: immerse the nano-magnesium oxide into a sufficient amount of sodium silicate solution, immerse it fully, the immersion power is 375W, the immersion time is 25min, and the immersion is completed to obtain the nano-magnesium oxide liquid;
[0119] S02: Stir the silicon carbide fiber in the acid solution and mix it thoroughly, then wash it with water, filter it and dry it to obtain dry silicon carbide fiber; add 6.5 parts of dry silicon carbide fiber and 4 parts of nano-magnesium oxide liquid to 9 parts of dopamine hydrochloride solution by weight and stir them thoroughly to obtain silicon carbide fiber / nano-magnesium oxide composite liquid;
[0120] S03: The silicon carbide fiber / nano-magnesium oxide composite liquid and the nano-hydroxyapatite agent are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1000 r / min for 2 h. After the ball milling is completed, the mixture is filtered and dried to obtain a nano-hydroxyapatite-modified bifunctional body.
[0121] The mass fraction of the sodium silicate solution in this embodiment is 3.5%; the acid solution is a sulfuric acid solution with a mass fraction of 5%; and the mass fraction of the dopamine hydrochloride solution is 4%.
[0122] The preparation method of the nano-hydroxyapatite agent in this embodiment is:
[0123] According to weight, 4 parts of nano-hydroxyapatite and 1.5 parts of citric acid are added to 6.5 parts of 5% sodium lignin sulfonate solution, and then 3 parts of nano-mica powder and 1.5 parts of samarium nitrate are added to improve the ball milling treatment. After the ball milling is completed, the mixture is filtered and dried to obtain a nano-hydroxyapatite agent.
[0124] The ball milling speed of the improved ball milling process in this embodiment is 600 r / min, and the ball milling is performed for 2.5 h.
[0125] The preparation method of the modified filler of this embodiment is:
[0126] S11: Evenly blending nano-titanium dioxide, chitosan solution and silane coupling agent KH550 in a weight ratio of 3.5:7:1 to obtain nano-titanium dioxide liquid;
[0127] S12: adding 4 parts of zirconium silicate and 2.5 parts of europium nitrate to 6.5 parts of lanthanum chloride solution by weight, and then adding 1.5 parts of sodium carboxymethyl cellulose, and mixing well to obtain a modifier;
[0128] The modifier and nano titanium dioxide liquid are stirred and modified in a weight ratio of 2:5.5. After the stirring is completed, the modified filler is filtered and dried to obtain a modified filler.
[0129] The mass fraction of the chitosan solution in this embodiment is 3.5%; the mass fraction of the lanthanum chloride solution is 3-5%; the stirring temperature of the stirring modification treatment is 57.5°C, the stirring time is 25min, and the stirring speed is 600r / min.
[0130] A method for preparing a self-cleaning ceramic in this embodiment comprises the following steps:
[0131] Step 1: 5.5 parts of clay, 6.5 parts of porcelain stone, 10 parts of calcined talc and 12.5 parts of illite are mixed and wet-milled by weight at a ball milling speed of 1500 r / min for 1 hour. After the ball milling is completed, the mixture is put into a mold for molding at a molding pressure of 15 MPa for 2 hours, and demolded to obtain a ceramic body;
[0132] Step 2: Melt 12.5 parts of potassium feldspar, 10 parts of nano zinc oxide, 6 parts of calcite and 5 parts of quartz by weight until the raw materials are completely melted, and then quench with water to obtain a glaze frit;
[0133] 17.5 parts of nano-hydroxyapatite-modified bifunctional body, 12.5 parts of glaze frit, 7.5 parts of modified filler, 5.5 parts of wollastonite and 4 parts of calcium carbonate were wet-milled by weight at a ball milling speed of 1500 r / min for 1 hour to obtain a self-cleaning glaze;
[0134] Step 3: Apply the self-cleaning glaze to the ceramic body, the amount of glaze applied is 565g / m 2 After the application is completed, the ceramic is sintered for 2 hours at a temperature of 1250°C to obtain self-cleaning ceramics.
[0135] The self-cleaning ceramic of this embodiment is prepared by the above-mentioned method for preparing the self-cleaning ceramic.
[0136] Comparative Example 1:
[0137] The difference from Example 3 is that no bifunctional body modified by nano-hydroxyapatite is added.
[0138] Comparative Example 2:
[0139] The difference from Example 3 is that silicon carbide fiber / nano-magnesium oxide composite is not added in the preparation of the bifunctional body based on nano-hydroxyapatite modification.
[0140] Comparative Example 3:
[0141] The difference from Example 3 is that no dry silicon carbide fiber is added in the preparation of the silicon carbide fiber / nano-magnesium oxide composite.
[0142] Comparative Example 4:
[0143] The difference from Example 3 is that no nano-magnesium oxide liquid is added in the preparation of the silicon carbide fiber / nano-magnesium oxide composite.
[0144] Comparative Example 5:
[0145] The difference from Example 3 is that no nano-hydroxyapatite-based agent is added in the preparation of the nano-hydroxyapatite-modified bifunctional body.
[0146] Comparative Example 6:
[0147] The difference from Example 3 is that no nano-hydroxyapatite and citric acid are added in the preparation of the nano-hydroxyapatite agent.
[0148] Comparative Example 7:
[0149] The difference from Example 3 is that no nano mica powder and samarium nitrate are added in the preparation of the nano hydroxyapatite agent.
[0150] Comparative Example 8:
[0151] The difference from Example 3 is that no modified filler is added.
[0152] Comparative Example 9:
[0153] The difference from Example 3 is that no nano titanium dioxide liquid is added to the modified filler.
[0154] Comparative Example 10:
[0155] The difference from Example 3 is that the nano titanium dioxide liquid is directly replaced by the nano titanium dioxide raw material.
[0156] Comparative Example 11:
[0157] The difference from Example 3 is that no modifier is added to the modified filler.
[0158] Comparative Example 12:
[0159] The difference from Example 3 is that zirconium silicate and sodium carboxymethyl cellulose are not added to the modifier.
[0160] Comparative Example 13:
[0161] The difference from Example 3 is that europium nitrate is not added to the modifier, and the lanthanum chloride solution is replaced by water.
[0162] The ceramic products of Examples 1 to 3 and Comparative Examples 1 to 13 were tested for anti-slip, wear resistance and antibacterial properties. At the same time, the products were placed under 2% hydrochloric acid mist conditions for 6 hours, and then placed under 5% sodium hydroxide alkaline mist conditions for 6 hours, and then scratched 10 times with a load force of 10N to test the stability of the products under acid and alkali and scratching conditions. The measurement results are shown in Table 1.
[0163] Table 1 Performance test results of ceramic products of Examples 1 to 3 and Comparative Examples 1 to 13:
[0164]
[0165] From Examples 1 to 3 and Comparative Examples 1 to 13, it can be concluded that the product of Example 3 has excellent E. coli antibacterial rate, anti-slip property and wear resistance, the product performance can achieve coordinated improvement, and the product has significant acid and alkali resistance and scratch stability effects;
[0166] The present invention does not add the bifunctional body based on nano-hydroxyapatite modification and does not add one of the modified fillers, and the performance of the product is significantly deteriorated. The two are used in combination to achieve synergistic effects, and the product performance effect is most significant;
[0167] In the preparation of the bifunctional body modified by nano-hydroxyapatite, no silicon carbide fiber / nano-magnesium oxide composite was added, no dry silicon carbide fiber was added in the preparation of the silicon carbide fiber / nano-magnesium oxide composite, no nano-magnesium oxide liquid was added in the preparation of the silicon carbide fiber / nano-magnesium oxide composite, no nano-hydroxyapatite agent was added in the preparation of the bifunctional body modified by nano-hydroxyapatite, no nano-hydroxyapatite and citric acid were added in the preparation of the nano-hydroxyapatite agent, and no nano-mica powder and samarium nitrate were added in the preparation of the nano-hydroxyapatite agent. The performance of the products showed a trend of deterioration to varying degrees;
[0168] The bifunctional body based on nano-hydroxyapatite modification prepared by the specific method of the present invention based on nano-hydroxyapatite agent and silicon carbide fiber / nano-magnesium oxide composite agent has the most significant performance effect of the product, and other methods are not as obvious as the effect of the present invention;
[0169] The performance of the products tended to deteriorate when no nano titanium dioxide liquid was added to the modified filler, the nano titanium dioxide liquid was directly replaced by nano titanium dioxide raw material, no modifier was added to the modified filler, zirconium silicate and sodium carboxymethyl cellulose were not added to the modifier, europium nitrate was not added to the modifier, and lanthanum chloride solution was replaced by water. The modified filler prepared by combining the modifier obtained by the specific method of the present invention with the nano titanium dioxide liquid had the most significant product performance effect. The modifier of the present invention was specific, and the technical effect of the present invention could not be achieved by replacing it by other methods.
[0170] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0171] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A self-cleaning glaze, characterized in that: It includes the following raw materials in parts by weight: 15-20 parts of bifunctional body modified based on nano-hydroxyapatite, 10-15 parts of glaze frit, 6-9 parts of modified filler, 4-7 parts of wollastonite and 3-5 parts of calcium carbonate; The preparation method of the bifunctional body based on nano-hydroxyapatite modification is: S01: immersing the nano-magnesium oxide into a sufficient amount of sodium silicate solution, the immersion power is 350-400W, the immersion time is 20-30min, and the immersion is completed to obtain the nano-magnesium oxide liquid; S02: stirring and mixing the silicon carbide fiber in the acid solution, then washing, filtering and drying to obtain dry silicon carbide fiber; Add 5 to 8 parts of dry silicon carbide fiber and 3 to 5 parts of nano-magnesium oxide liquid to 7 to 11 parts of dopamine hydrochloride solution by weight and stir thoroughly to obtain a silicon carbide fiber / nano-magnesium oxide composite liquid; S03: mixing the silicon carbide fiber / nano-magnesium oxide composite liquid and the nano-hydroxyapatite agent in a weight ratio of 5:3, and ball milling the mixture at a speed of 1000 r / min for 2 h. After the ball milling is completed, the mixture is filtered and dried to obtain a nano-hydroxyapatite-modified bifunctional body; The preparation method based on the nano-hydroxyapatite agent is: According to weight, 3-5 parts of nano-hydroxyapatite and 1-2 parts of citric acid are added to 5-8 parts of 5% sodium lignin sulfonate solution, and then 2-4 parts of nano-mica powder and 1-2 parts of samarium nitrate are added to improve the ball milling treatment. After the ball milling is completed, the mixture is filtered and dried to obtain a nano-hydroxyapatite agent; The glaze frit comprises the following raw materials in parts by weight: 10-15 parts of potassium feldspar, 8-12 parts of nano zinc oxide, 5-7 parts of calcite and 4-6 parts of quartz; The preparation method of the modified filler is: S11: Evenly blend nano-titanium dioxide, chitosan solution and silane coupling agent KH550 in a weight ratio of (3-4):(6-8):1 to obtain nano-titanium dioxide liquid; S12: adding 3 to 5 parts of zirconium silicate and 2 to 3 parts of europium nitrate to 5 to 8 parts of lanthanum chloride solution by weight, and then adding 1 to 2 parts of sodium carboxymethyl cellulose, and mixing well to obtain a modifier; The modifier and nano titanium dioxide liquid are stirred and modified in a weight ratio of 2:(5-6). After the stirring is completed, the modified filler is filtered and dried to obtain a modified filler.
2. The self-cleaning glaze according to claim 1, characterized in that: The mass fraction of the sodium silicate solution is 2-5%; the acid solution is a sulfuric acid solution with a mass fraction of 5%; and the mass fraction of the dopamine hydrochloride solution is 3-5%.
3. The self-cleaning glaze according to claim 1, characterized in that: The ball milling speed of the improved ball milling treatment is 550-750 r / min, and the ball milling is 2-3 hours.
4. The self-cleaning glaze according to claim 1, characterized in that: The mass fraction of the chitosan solution is 2-5%; the mass fraction of the lanthanum chloride solution is 3-5%.
5. The self-cleaning glaze according to claim 1, characterized in that: The stirring temperature of the stirring modification treatment is 55-60° C., the stirring time is 20-30 min, and the stirring speed is 550-750 r / min.
6. A method for preparing self-cleaning ceramics, characterized in that: The following steps are involved: Step 1: 4-7 parts of clay, 5-8 parts of porcelain stone, 8-12 parts of calcined talc and 10-15 parts of illite are mixed and wet-milled by weight at a ball milling speed of 1500 r / min for 1 hour. After the ball milling is completed, the mixture is put into a mold for molding at a molding pressure of 15 MPa for 2 hours, and demolded to obtain a ceramic body; Step 2: melting 10-15 parts of potassium feldspar, 8-12 parts of nano zinc oxide, 5-7 parts of calcite and 4-6 parts of quartz by weight until the raw materials are completely melted, and then quenching with water to obtain a glaze frit; 15-20 parts of nano-hydroxyapatite modified bifunctional body, 10-15 parts of glaze frit, 6-9 parts of modified filler, 4-7 parts of wollastonite and 3-5 parts of calcium carbonate are wet-milled by weight at a ball milling speed of 1500 r / min for 1 hour to obtain a self-cleaning glaze; The preparation method of the bifunctional body based on nano-hydroxyapatite modification is: S01: immersing the nano-magnesium oxide into a sufficient amount of sodium silicate solution, the immersion power is 350-400W, the immersion time is 20-30min, and the immersion is completed to obtain the nano-magnesium oxide liquid; S02: stirring and mixing the silicon carbide fiber in the acid solution, then washing, filtering and drying to obtain dry silicon carbide fiber; Add 5 to 8 parts of dry silicon carbide fiber and 3 to 5 parts of nano-magnesium oxide liquid to 7 to 11 parts of dopamine hydrochloride solution by weight and stir thoroughly to obtain a silicon carbide fiber / nano-magnesium oxide composite liquid; S03: mixing the silicon carbide fiber / nano-magnesium oxide composite liquid and the nano-hydroxyapatite agent in a weight ratio of 5:3, and ball milling the mixture at a speed of 1000 r / min for 2 h. After the ball milling is completed, the mixture is filtered and dried to obtain a nano-hydroxyapatite-modified bifunctional body; The preparation method based on the nano-hydroxyapatite agent is: According to weight, 3-5 parts of nano-hydroxyapatite and 1-2 parts of citric acid are added to 5-8 parts of 5% sodium lignin sulfonate solution, and then 2-4 parts of nano-mica powder and 1-2 parts of samarium nitrate are added to improve the ball milling treatment. After the ball milling is completed, the mixture is filtered and dried to obtain a nano-hydroxyapatite agent; The preparation method of the modified filler is: S11: Evenly blend nano-titanium dioxide, chitosan solution and silane coupling agent KH550 in a weight ratio of (3-4):(6-8):1 to obtain nano-titanium dioxide liquid; S12: adding 3 to 5 parts of zirconium silicate and 2 to 3 parts of europium nitrate to 5 to 8 parts of lanthanum chloride solution by weight, and then adding 1 to 2 parts of sodium carboxymethyl cellulose, and mixing well to obtain a modifier; The modifier and the nano titanium dioxide liquid are stirred and modified in a weight ratio of 2:(5-6), and after the stirring is completed, the modified filler is filtered and dried to obtain a modified filler; Step 3: Apply the self-cleaning glaze to the ceramic body, the amount of glaze applied is 550-580g / m 2 After the application is completed, the ceramic is sintered for 2 hours at a temperature of 1250°C to obtain self-cleaning ceramics.
7. A self-cleaning ceramic prepared by the method for preparing a self-cleaning ceramic according to claim 6.
Citation Information
Patent Citations
Ceramic product with self-cleaning glaze and making method thereof
CN109437839A
Self-cleaning nano ceramic glaze convenient to clean and preparation method of self-cleaning nano ceramic glaze
CN111204977A